2019
DOI: 10.22317/jcms.v5i5.683
|View full text |Cite
|
Sign up to set email alerts
|

Premalignant changes associated chronic gastritis in Karbala Province: multi institutional study

Abstract: Objectives: The aim of this study was to investigate the prevalence of gastric premalignant changes as gastric atrophy, intestinal metaplasia and dysplastic changes in patients underwent esophagogastroduodenoscopy in three health institutions in Karbala province. Methods: The data was collected from patients attended the endoscopy units during a period from January  to September 2018 in three medical centers in holy Karbala/ Iraq, Al Hussein teaching hospital, Imam Zain Al Abedin hospital and Imam AL Huj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…The incidence of CRC is increasing annually worldwide. The demographics of the CRC group were similar to those of the patients in most of the studies conducted in Iraq, such as those by Radhi et al 20 in Al-Diwaniyah, by Alsafi et al 21 in Karbala, by Alshewered and Al-Naqqash 2 and by Alrubaia et al 3 in Baghdad, but differed from the demographics found in the studies by Alhilfi et al 4 in Misan, and by Khalil et al 22 in Duhok. In Western countries, 8% of the CRC cases are recorded in patients younger than 40 years of age, whereas in Asia and Africa the rates range between 15% and 35% for the same age group.…”
Section: Discussionsupporting
confidence: 64%
“…The incidence of CRC is increasing annually worldwide. The demographics of the CRC group were similar to those of the patients in most of the studies conducted in Iraq, such as those by Radhi et al 20 in Al-Diwaniyah, by Alsafi et al 21 in Karbala, by Alshewered and Al-Naqqash 2 and by Alrubaia et al 3 in Baghdad, but differed from the demographics found in the studies by Alhilfi et al 4 in Misan, and by Khalil et al 22 in Duhok. In Western countries, 8% of the CRC cases are recorded in patients younger than 40 years of age, whereas in Asia and Africa the rates range between 15% and 35% for the same age group.…”
Section: Discussionsupporting
confidence: 64%